The interval robotic transabdominal cerclage in a morbidly obese patient. Issue 1 (March 2016) - Güngör, Mete; Afşar, Selim; Özbaşlı, Esra; Genim, Canan
Abstract The most commonly used prophylactic treatment of cervical insufficiency is cerclage but it carries significant morbidity either through vaginal or abdominal approach. A robotic-assisted transabdominal cerclage (RoboTAC) placement as an interval procedure could offer advantages over the conventional laparoscopic approach especially in morbidly obese patients. We report the use of interval RoboTAC procedure in a morbidly obese patient and ultimately she delivered a healthy infant at 38 weeks 2 days nonetheless removal of the cerclage.